EVALUATION MODEL FOR INFORMATION SYSTEMS BASED ON SYSTEM QUALITY FACTORS: FROM A SYSTEM DEVELOPER PERSPECTIVE - Kamsuriah Ahmad; Mohd Reffi Hidayat Roslan, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Information system (IS) is seen to be one of the major factors that operate the organization systematically and has contributed a positive impact in improving the performance of an organization. Due to its importance, many studies have done in ensuring the best method employed in its development and comply with its quality. The challenges are to identify a method in evaluating the quality of the systems and this has become the interest of many researchers. There are various evaluation models exist, in fact, various evaluation theories have been proposed in different disciplines and perspectives. However, the existing evaluations are based from the user's perspective and often ignored the point of view from the system developers. System developers are the persons who are responsible to develop the system. They are responsible in ensuring the systems comply with its quality and making the system usable, effective and error free. System developers also ensure that the developments are according to the user specifications. Therefore, their views in determining the quality of the system should be taken into account. Thus the aim of this study is to propose an evaluation model for IS based on system quality factor from the perspective of system developers. The findings showed that the system quality factors such as data quality, user satisfaction and organizational needs are the factors that should take into account when proposing IS evaluation models. The findings from this study could be served as a guideline to the system development team in producing quality systems that are able to enhance organizational performance.